2020
DOI: 10.2340/16501977-2667
|View full text |Cite
|
Sign up to set email alerts
|

Level of physical activity is positively correlted with perceived impact on life 12 months after stroke: A cross-sectional study

Abstract: It is common for stroke survivors to experience longterm symptoms. This study investigated individuals' perceptions of how stroke symptoms impact on their lives, and examined the connection between this and their level of physical activity 12 months after stroke. A total of 73 stroke survivors completed 2 questionnaires; about their level of physical activity, and their perception of how their life is impacted by stroke. The results showed that a higher level of physical activity at 12 months after stroke was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As the SGPALS is an easy-to-use measurement tool for selfreported PA, it has been used in several large-scale population-based studies, also in Denmark [31][32][33][34][35]. SGPALS has been used in patients with stroke [36][37][38][39], but never in patients with MG.…”
Section: Physical Activity Levelmentioning
confidence: 99%
“…As the SGPALS is an easy-to-use measurement tool for selfreported PA, it has been used in several large-scale population-based studies, also in Denmark [31][32][33][34][35]. SGPALS has been used in patients with stroke [36][37][38][39], but never in patients with MG.…”
Section: Physical Activity Levelmentioning
confidence: 99%
“…On one hand, many stroke survivors do not achieve the recommended amount of physical activity according to the WHO (WHO, 2010;Bull et al, 2020;Fini et al, 2017). On the other hand, it has been reported that an increased physical activity after a stroke could improve recovery (Cook, 2020) and quality of life (Belfiore, 2018), reduce disability (Saunders et al, 2016) and improve cognitive function (Kim et al, 2019), and potentially affect sleep, depressive symptoms and fatigue.…”
Section: Introductionmentioning
confidence: 99%